PELAKSANAAN PENGAWASAN SATUAN PENGAWASAN KETENAGAKERJAAN WILAYAH SEMARANG TERHADAP TENAGA KERJA ASING DI KABUPATEN SEMARANG - Septianingrum, Arum; Taufiq, Ahmad (Journal of Politic and Government Studies, 2018)
The control implementation of labor control unit of Semarang on foreign labor in Semarang regency has the purpose to explain the supervision on the workforce conducted by the Labor Control Unit of Semarang region in supervising the foreign worker in Semarang regency and what obstacles influence in the implementation of supervision on foreign worker in Semarang regency.This research uses descriptive qualitative method where the writer use information from agency of Labor Office and Labor Inspection Unit in Semarang Region and also outsider as balancing data, that is companies in Semarang regency on PT Samkyung Jaya Garment, PT Hoplun, dan PT Hesed Indonesia.The results of this study indicate that the control implementation of foreign workers is seen in the main tasks and functions of the Labor Inspection Unit of Semarang region through administrative supervision or licensing the use of foreign workers, and direct supervision with guidance and field inspection activities.This is done in Semarang regency because the area is an industrial area where the use of foreign labor quite a lot amount of 170 person at 49 companies (data agency of Labor Office, 2015).The control implementation of foreign workers in Semarang requires cooperation between supervisory agencies, companies that employ foreign workers and the public. The existence of supervision on foreign workers not only aims to prevent the existence of illegal foreign workers in Semarang regency but also to increase the transfer of expertise in encouraging equal distribution of employment opportunities for local workers.Supervision conducted through direct supervision such as guidance on the regulation of the use of foreign workers and field inspections, as well as indirect supervision is done through licensing procedures with the standard of labor regulations.Obstacles in the control implementationof foreign workers in Semarang Regency are the use of third parties (agents) in the management of foreign worker permits, lack of specification of certain competency standards in certification of transfer of expertise and salary differences.The conclusion of the research is in carrying out supervision on foreign workers there is a link with the labor inspectors so that the need for labor inspection to achieve the equalization of employment opportunities.Keywords : Labor Inspection, Foreign Worker, and Labor Inspection Unit